2019
DOI: 10.1002/pon.5281
|View full text |Cite
|
Sign up to set email alerts
|

Brief culturally informed smartphone interventions decrease breast cancer symptom burden among Latina breast cancer survivors

Abstract: Objective: Latina breast cancer survivors (BCS) report more symptom burden and poorer health-related quality of life than non-Latina BCS. However, there are few evidence-based and culturally informed resources that are easily accessible to this population. This study aimed to establish the feasibility and preliminary efficacy of the My Guide and My Health smartphone applications among Latina BCS. Both applications are culturally informed and contain evidence-based information for reducing symptom burden and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 39 publications
1
80
0
Order By: Relevance
“…Our results showed that women positively valued the app as a tool to obtain information and counseling about HPV and CC. Similar findings were reported by studies that analyzed women’s preference for apps aimed at providing support to women diagnosed with cancer [ 43 , 76 - 80 ]. Two studies analyzed the acceptability of an app oriented toward educating people on HPV and CC prevention.…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that women positively valued the app as a tool to obtain information and counseling about HPV and CC. Similar findings were reported by studies that analyzed women’s preference for apps aimed at providing support to women diagnosed with cancer [ 43 , 76 - 80 ]. Two studies analyzed the acceptability of an app oriented toward educating people on HPV and CC prevention.…”
Section: Discussionsupporting
confidence: 86%
“…We will assess acceptability with author-constructed questions which ask participants to rate how much they enjoyed the information presented in the weekly group sessions and how much they liked the weekly online groups in general [ [43] , [44] , [45] , [46] ]. Items are rated on a 5-point scale ranging from 1 (a lot) to 5 (did not review).…”
Section: Methodsmentioning
confidence: 99%
“…The welcome video was included based on user feedback gathered early in the course of this usability testing. The majority of the content in My NM Care Corner was derived from previous technology-assisted pilot studies that focused on improving patient symptom management and health-related quality of life among diverse patients with cancer diagnoses [12][13][14][15][16]. In My NM Care Corner, symptoms flagged as elevated based on ePRO responses are visible to users when they access their dashboard.…”
Section: Prototype Developmentmentioning
confidence: 99%
“…Thus, although we determined that the prototype of My NM Care Corner was rated as highly usable in concept and was viewed as generally easy to navigate, this phase of the usability testing did not extend to an examination of the usability of clinical content. However, the majority of content in My NM Care Corner was derived from previous technology-assisted pilot studies that focused on improving patient symptom management and health-related quality of life among diverse patients with cancer diagnoses, and thus have support for acceptability [12][13][14][15][16].…”
Section: Limitationsmentioning
confidence: 99%